Pancreaticoduodenal Artery Aneurysms in Association with Celiac Axis Compression Syndrome - Miyasaka, Daisuke; Kato, Hiroyuki; Kitashiro, Shuji; Nitta, Takeo; Okushiba, Shunichi; Kawarada, Yo; Sasaki, Takeshi; Ebihara, Yuma (The Japanese Journal of Gastroenterological Surgery, 2011)
A 59-year-old woman with acute abdominal and back pain was referred with a diagnosis of pancreaticoduodenal artery aneurysms. Preoperative abdomen contrast computed tomography (CT) revealed a retroperitoneal hematoma around the pancreatic head. Angiography indicated a hypertrophic pancreaticoduodenal arcade and two pancreaticoduodenal artery aneurysms, together with retrograde hepatic, splenic, and left gastric artery flow via the gastroduodenal artery. We evaluated the blood flow of the common hepatic artery and aneurysms intraoperatively using indocyanine green (ICG) fluorescence imaging. Our findings suggested celiac artery trunk compression with multiple pancreaticoduodenal artery aneurysms. Surgery involved ligating the aneurysm branches and dividing the median arcuate ligament.